Euphemisms in advertising discourse: Putting on a positive face and maintaining speech etiquette - Elena A. Danilina; Ekaterina E. Kizyan; Daria S. Maksimova (Peoples' Friendship University of Russia (RUDN University), 2019)
The study describes advertising discourse as unique in terms of its manipulative potential and attempts to observe the way euphemistic units are used in English commercial and social advertising. The authors highlight the two key functions: a 'call-to-action' function of commercial ads and the 'raising awareness' function of social ads. The study relies on the theory of politeness and the concept of face suggested by Brown and Levinson to apply the same principles in the analysis of English advertising texts. The authors consider different categories of goods and end products in both commercial and social advertising discourse to identify the main goals and strategies behind euphemisation as a manipulating mechanism and a language tool allowing to observe the socially accepted standards of speech etiquette.